Null Curriculum: Neglected or ineffective - Habibolah Rezaei; Nikoo Yamani (مجله ایرانی آموزش در علوم پزشکی, 2017)
Introduction: Null curriculum is one type of curriculum. In relation to this type of curriculum, little research has been carried out in the world indicating the neglect of this concept. The aim of this study was to review the concept of null curriculum from different viewpoints. Methods: In this review study, the databases of SID, Iranmedex, Irandoc, and Magiran, Pubmed central, Eric and Google scholar were reviewed using the keywords null curriculum, neglected curriculum, omitted curriculum, neutral curriculum and ineffective curriculum. Results: Search results yielded 70 articles and 15 books that were somehow related to null curriculum. After the reviews, 18 articles and books that were closer to the research goal were selected. Two perspectives of curriculum planning experts and medical education experts were identified on null curriculum. The former believe that null curriculum is the neglected curriculum while the latter state that null curriculum is the ineffective curriculum. Conclusion: Considering the different definitions of null curriculum from the viewpoints of curriculum planning experts and medical education experts, it is recommended that those who want to have a practical use of this concept should first ground their definition on one of these viewpoints in order to avoid confusion.